2015
DOI: 10.5588/ijtld.13.0819
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin pharmacokinetics in children under the Revised National Tuberculosis Control Programme, India, 2009

Abstract: Low serum concentrations of RMP were attained in children under the RNTCP 2009 weight band system. Peak RMP levels appear to be lower and the single dose elimination half-life shorter in children than in adults. To optimise treatment outcomes, revisions in RMP dose in children should take into consideration age-related differences in pharmacokinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Table 1 shows the breakdown between favorable and unfavorable outcomes and loss to follow-up, as reported by the individual studies. Reported risk factors for unfavorable outcomes included lower drug exposures, including for RIF [ 23 , 26 , 29 ], INH [ 19 , 23 ], and PZA [ 24 ], as well as lower weight for age [ 19 ] or severe malnutrition [ 36 ], poor social circumstances [ 15 ], and severity of infection [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the breakdown between favorable and unfavorable outcomes and loss to follow-up, as reported by the individual studies. Reported risk factors for unfavorable outcomes included lower drug exposures, including for RIF [ 23 , 26 , 29 ], INH [ 19 , 23 ], and PZA [ 24 ], as well as lower weight for age [ 19 ] or severe malnutrition [ 36 ], poor social circumstances [ 15 ], and severity of infection [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“… Percentage of reported favorable outcomes per study, with the risk factors identified in the listed publications [ 14 , 15 , 19 , 20 , 23 , 24 , 26 , 29 , 30 , 33–35 ]. Colors indicate whether children in the study received World Health Organization (WHO)–recommended doses of first-line antituberculosis agents or doses based on Revised National Tuberculosis Control Program guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in India report mixed findings (0-58.7% attaining the recommended targets); however, the studies offer a clear indication that the likelihood of achieving adequate concentrations increases with increasing age. 16,[42][43][44] Importantly, adult studies indicate that a substantial fraction of adults similarly fail to attain the recommended pharmacodynamics target for rifampin, highlighting the large degree of inter-individual variability in rifampin PK and the degree of uncertainty in the recommendation that concentrations at 2 hours exceed 8 µg/mL. 22 It is also important to recognize that many of the pediatric studies described above report favorable clinical outcomes in children despite failure to meet pharmacodynamics targets.…”
Section: Rifampinmentioning
confidence: 99%
“…22 It is also important to recognize that many of the pediatric studies described above report favorable clinical outcomes in children despite failure to meet pharmacodynamics targets. 20,42 Nonetheless, pharmacokinetic modeling coupled with accumulated practical experience is leading experts to recommend pediatric doses of at least 15 to 20 mg/kg and upward of 30 mg/kg while treating CNS infection. [45][46][47]…”
Section: Rifampinmentioning
confidence: 99%